"Eu sou um gamer e um cosplayer": consumo de games míticos e sua repercussão na prática cosplay - Sá, Davi Naraya Bastos de (2014)
This research aims to study the consumption of games based on mythologies, named mythic games, and its repercussion in cosplay practice. It recognizes the existence of two mythological-narrative matrices as logics to the production of other cultural texts, as for example, the games and cosplays analyzed in this study. The research starts by demonstrating the importance of the consumption of games in the current society by the writings of Mike Featherstone, Grant McCracken, among others. After that, based on studies concerning the mythological structures found in the researches carried out by Mircea Eliade, the first narrative matrix is identified through the evaluation of the Pokémon game and by observing how this game counted on mythological structures to create its own narrative. The second matrix is obtained when evaluating the Age of Mythology, where the use of existing mythology was perceived, as well as its translation, for the production of the game narrative. Such translation is indeed a transcreation, based on Haroldo de Campos studies. In the third part, this study discusses the practice of cosplay, observing how youth get dressed and act as media characters specially when representing mythic games. This research counts on results from fieldwork approaches at anime events, where cosplays get together in the capital of the state of São Paulo, as well as on documents collected in events held in the city of Rio de Janeiro. Here, evaluations followed the considerations proposed by Nunes and by Perper and Cornog. Mythology, it seems, is still nowadays a widely-consumed product. Consumption can be found in tangible, symbolic and media dimensions but also as a sense of belonging and identification propelling, not to mention its link to communication and culture, perceived as memory.